Attraction of Cultural Festival on Travel Destination - Nuryulia Praswati, Aflit; Nur Tikarina, Qori; Fauziyah Fadhali, Alfi (KnE Social Sciences, 2020)
The ancestral cultural heritage is a unique wealth of an area and must be preserved so that it can provide economic benefits to the surrounding community. This preservation can be done by actively holding cultural festivals. Organizing a cultural festival involves quite a lot of stakeholders, such as the government, the private sector, and also the community. This study aims to determine the role and impact received by stakeholders with the implementation of cultural festivals in Surakarta City. The qualitative research method used in study 1 is to find out the impact of organizing cultural festivals and quantitative methods in study 2 used to analyze the behavior of visitors to cultural festivals. Study 1 gets interesting results where each stakeholder has an important role to play in achieving the success of a cultural festival. Study 2 in this study found that motivation, perceived value and experience as antecedents of revisit intention. Keywords: motivation, perceived value, experience, revisit intention